365 science activities Usborne activities - Lacey, Minna (London : Usborne Publishing Ltd., 2014)
This colorful, hands-on activity book offers a year$1 (Bs worth of simple science experiments and projects for children. Covering topics like plants, animals, weather, forces, materials, and the human body, each activity is explained with clear, step-by-step instructions and lively illustrations. Designed to spark curiosity, it encourages kids to explore scientific ideas using everyday materials, making learning both fun and practical.s
Keywords: General Science - Reference Book